Plants and fungi in the ethnomedicine of the medieval East - a review - Tayjanov, Karimjon; Khojimatov, Olim; Gafforov, Yusufjon; Makhkamov, Trobjon; Normakhamatov, Nodirali; Bussmann, Rainer W (Ethnobotany Research and Applications, 2021)
Background: In the history of medicinal science of the medieval East, the merits of the great tabibs-physicians Ar-Razi, Avicenna (Ibn Sinо), the scientist-encyclopedist Beruni, Yusufi and others are enormous. When treating patients, they used medicinal plants, as well as fungi, animal (ornithological) and mineral products. Such use of plants for medicinal purposes goes back centuries. In this review, we present a compilation of the most important plant species and fungi used in the traditional medicine of the medieval East. Methods: We have obtained ethnomedicinal information by searching various resources, such as scientific and popular journal papers, monographs, books written in Uzbek, Russian and English, and our materials focused on the traditional use of medicinal plants and fungi. Scientific names, both of plants and fungi were checked for potential synonyms in the databases Index Fungorum and Plants of the World Online (POWO). Results: Based on literary data on taxonomy, resource science, as well as folk and scientific medicine, we compiled a list of plant families used by healers and medicines of the Middle East. According to our results, 173 species of medicinal plants were used and described by Ar-Razi, 515 by Avicenna, 901 in Beruni, and 110 as well as a few fungal species in Yusufi. Among the medicinal plants used by Ar-Razi, Avicenna and the Beruni listed in Saidana are more than 240 species currently found in the flora of Uzbekistan. Conclusion: On the face of the fact that the centuries-old experience of traditional medicine, generalized in the works of scientists from the Middle East, has found its confirmation at the present time. Most of the medicinal plants indicated by them are now included in the Pharmacopoeias of many countries, from which both independent medicinal products were obtained, and biologically active substances were isolated that serve in the improvement of the population. Given the growing interest in medicines of natural origin, work in this direction will continue. Key words: Ethnobiology, Plants, Fungi, Folk Medicine, Scientific Medicine